New speed training model for 15-17 year-old cross-country skiers - Gerasimov, N. P.; Ahmetshina, E. I.; Mutaeva, I. Sh.; Solomakhin, O. N. (Theory and Practice of Physical Culture, 2021)
Objective of the study was to theoretically substantiate and test benefits of a new preparatory-period speed training model for the 15-17 year-old cross-country skiers.